2023
DOI: 10.3390/ijms24021377
|View full text |Cite
|
Sign up to set email alerts
|

Does the Composition of Gut Microbiota Affect Hypertension? Molecular Mechanisms Involved in Increasing Blood Pressure

Abstract: Arterial hypertension is a chronic disease which is very prevalent contemporarily. The aim of this review was to investigate the impact of gut microbiota on the development and potential treatment of hypertension, taking into consideration underlying molecular mechanisms. The bacteria present in the intestines have the ability to secrete different metabolites, which might play a significant role in the regulation of blood pressure. The most important include short-chain fatty acids (SCFAs), vasoactive hormones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 83 publications
0
5
0
1
Order By: Relevance
“…Moreover, the gut microbiota has a genuine effect on both diabetes and CVDs. Due to the fact that these diseases could lead to severe complications for the patient, relying entirely on probiotics may be insufficient; however, it is highly recommended to enrich the treatment with the intake of probiotics [145]. Further research on this topic is needed to fully establish the composition of the most-effective probiotic treatment in both CVDs and diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the gut microbiota has a genuine effect on both diabetes and CVDs. Due to the fact that these diseases could lead to severe complications for the patient, relying entirely on probiotics may be insufficient; however, it is highly recommended to enrich the treatment with the intake of probiotics [145]. Further research on this topic is needed to fully establish the composition of the most-effective probiotic treatment in both CVDs and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The most popular type of probiotics consists of the four most-common species: Streptococcus sp. Bifidobacterium sp., Lactobacillus sp., and Enterococcus sp., and their sources might be dietary such as yogurt, cheese, or fermented products, which could present beneficial effects if consumed on a regular basis [144,145].…”
Section: Cardiovascular Disease Alteration Of Bacterial Metabolitesmentioning
confidence: 99%
“…Additionally, flavonoids have been reported to have vasodilatory and antihypertensive effects [49] . The phytochemical indole-3-carbinol, which is obtained from cruciferous vegetables, has demonstrated anti-inflammatory, antioxidant, antihypertensive, and antiarrhythmic properties [50] . Anti-inflammatory and antioxidant properties of some microbial metabolites may help regulate BP and have great potential for therapeutic treatments [51] .…”
Section: What Impact Does the Gut Microbiota Have On Blood Pressure?mentioning
confidence: 99%
“…The mechanisms of the gut microbiota impact on the development and progression of NAFLD and AH are caused by complex interactions between the gut microbiota and the host organism. Likely factors include metabolism of choline, bile acids, and amino acids resulting in synthesis of vasoactive hormones, such as trimethylamine (TMA) and trimethylamine N-oxide (TMAO), uremic toxins (indoxyl sulfate and p-cresol sulfate), as well as production of short-chain fatty acids (SCFAs) and ethanol by intestinal microorganisms [ 94 , 95 ]. Next, we discuss the role of SCFAs, TMA, and intestinal permeability in the pathogenesis of both AH and NAFLD.…”
Section: Mechanisms Of the Relationship Between Nafld And Ahmentioning
confidence: 99%
“…The most important and biologically active SCFAs include acetate, propionate, and butyrate; they are made from dietary fiber in the intestines. Regarding their role in the pathogenesis of AH, animal studies suggested that SCFAs may have both hypotensive and hypertensive effects depending on the receptors they bind to [ 95 , 96 ]. For instance, propionate-induced activation of the G protein-coupled receptor (GPR) 42 in vascular endothelium caused a decrease in BP in Olfr78−/− mice [ 97 ].…”
Section: Mechanisms Of the Relationship Between Nafld And Ahmentioning
confidence: 99%